HOW IS SAFE GENETICALLY MODIFIED FOOD? - Edmond Febrinicko Armay (Kodepena (Komunitas Dosen Penulis dan Peneliti Indonesia), 2021)
Genetically modified food is a kind of food that has been genetically enhanced through genetic engineering. Genetically modified food exists because people are too far from their food sources. Scientists and regulators point out that genetically modified food is not more risky than conventional plant breeding technology. This paper will investigate the potential risks of genetically modified food and provide a number of specific solutions to those disadvantages. It will then argue that consuming genetically modified food is generally safe. genetically modified food has to meet the same safety requirements as food grown from non-genetically-modified seeds. While genetically modified food has its pros and cons, genetically modified food is generally safe and healthy to eat, although research on its health effects is still limited. Despite these concerns, genetically modified food can help government find sustainable ways to feed people, specifically in countries that lack access to nutrient-rich food.